Hubungan Antara Strategi Employer Branding dan Kualitas Rekrutmen Terhadap Retensi Karyawan dalam Perusahaan Start-Up di Kota Surabaya - Eric Annasyah; Rifki Suwaji (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The high level of talent competition, demands for flexible work, and rapid organizational dynamics make start-up companies vulnerable to high employee turnover. This condition indicates that employee retention is a strategic challenge, especially when the company's image as a workplace and the quality of the recruitment process are not optimally managed. Employer branding plays a role in building positive perceptions of the organization, while recruitment quality determines the fit between employees, jobs, and company culture. Based on these problems, this study aims to analyze the influence of employer branding strategies and recruitment quality on employee retention in start-up companies in Surabaya. The study used a quantitative explanatory approach with a survey design. The sample consisted of 120 start-up employees selected through purposive sampling with a minimum work period of six months. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression. The results showed that employer branding strategies and recruitment quality each had a positive and significant effect on employee retention, both partially and simultaneously. These findings confirm that employee retention is influenced not only by financial factors, but also by company image and the accuracy of the recruitment process. This study provides strategic implications for start-ups in designing sustainable HR policies.